Myocilin as a Potential Factor for the Fast Type Change in the Muscle Isoform Composition: A Mini Review - Yunsuk Choi; Hyunseok Jee (Asian Society of Kinesiology, 2023)
BACKGROUND Various factors-based properties of the skeletal muscle are determined by mechanical stress, chemical stimuli, neuromuscular stimuli, different protein isoforms etc. The properties of the muscle are formed in the process of the balance between anabolism and catabolism. Especially, the anabolism on the way of the cell proliferation to its differentiation is accompanied by various controlling signal pathways. OBJECTIVE The purpose of this study focused on the mTOR/S6K system, Myosin, and Myocilin among these signaling pathways, especially on previously reported studies on the contribution of Myocilin to the skeletal muscle fiber type transformation. METHODS To identify the molecular pathways related to muscle development, the KEGG Mapper was used to present the mTOR-related signaling system that has not been identified so far. RESULTS Consequently, it suggests that it affects the myogenic process, through the path of PI3K->AKT->MEF2->MyoC->mTOR->p70S6K->S6. CONCLUSIONS It also suggests that Myocilin serves as a potential effector to control skeletal muscle cell type. Furthermore, more detailed study on the potential target-oriented (to the fast or slow fiber type change) role of Myocilin for enhancing the health state by adjusted exercise programs developed by its optimal type, intensity, frequency, and time is awaited.